2022
DOI: 10.1177/26350106221099872
|View full text |Cite
|
Sign up to set email alerts
|

Care Partner Support Following a Diabetes Self-Management Education and Support Intervention

Abstract: Purpose: The purpose of the study was to understand care partner (CP) perceptions of an interdisciplinary diabetes self-management education and support (DSMES) intervention and explore how the interdisciplinary DSMES intervention influences diabetes-specific day-to-day interactions from the CP’s perspective. Methods: A multiple-methods research design comprised of an online survey including demographics and supportive behaviors and a semistructured interview was conducted. The survey was completed by 16 CPs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
4
1
Order By: Relevance
“…Similarly, Pamungkas et al found a positive decline in A1C when providing comfort and encouragement for older adults who face distress or frustration of their diabetes care due to cognitive impairment ( Pamungkas & Chamroonsawasdi, 2020 ). However, our findings related to other types of family support (e.g., medication management and meal planning) were inconsistent with the reported literature ( Mansfield et al, 2022 ). These diabetes self-management tasks may require unique knowledge and skills, indicating that family members of individuals with cognitive impairment may need additional support or training to better assist with such types of diabetes self-management.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similarly, Pamungkas et al found a positive decline in A1C when providing comfort and encouragement for older adults who face distress or frustration of their diabetes care due to cognitive impairment ( Pamungkas & Chamroonsawasdi, 2020 ). However, our findings related to other types of family support (e.g., medication management and meal planning) were inconsistent with the reported literature ( Mansfield et al, 2022 ). These diabetes self-management tasks may require unique knowledge and skills, indicating that family members of individuals with cognitive impairment may need additional support or training to better assist with such types of diabetes self-management.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings indicate that strong family support in testing sugar and in handling feelings about diabetes was significantly associated with lower A1C, which is consistent with other reported studies ( Baig et al, 2015 ; Ritchie et al, 2020 ; Trief et al, 2016 ). Mansfield et al found that care partners played a significant role in patient diabetes self-management, particularly in making decisions about medication administration and glucose checks, meal planning and preparation, participating in physical activity, and assisting with technology ( Mansfield et al, 2022 ). Trief et al (2016) found that people with diabetes involved in a telephone educational offering with a partner had decreased depression compared with those receiving individual education.…”
Section: Discussionmentioning
confidence: 99%
“…Although they do more minutes of exercise per week, the days they exercise are the same as family members with support. 18 On the other hand, PDM have lower cholesterol levels, possibly due to having drug treatment, while unsupported family members have higher levels, as they do not seek medical care or check-ups if they do not have diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…As a problem, they expressed difficulty in helping their PDM without being overwhelming or “bothering” them. 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation